Well-dispersed Pt nanodots interfaced with Ni(OH)2 on anodized nickel foam for efficient hydrogen evolution reaction. (16th October 2020) - Gu, Yanfang; Wang, Yuanqiang; Shi, Junhui; Yang, Mengru; Rui, Yichuan; An, Wei; Men, Yong
Abstract: Hindered by price and scarcity, the exploitation of supported Pt-based electrocatalysts with Pt single atoms or Pt nanoclusters is an alternative way to decrease the dosage of Pt and improve the electrocatalytic performance for hydrogen evolution reaction (HER) of water splitting. The anodization technology is used to modify the surface of nickel foam (NF) to form the porous NiF2 network structure. Then Pt nanodots interfaced with Ni(OH)2 (Pt/Ni(OH)2 ) hybrid on the anodized NF has been in-situ synthesized by a simple hydrothermal decomposition method. Results show that Pt nanodots on the substrate have good dispersion with the average size of 3 nm, and the Pt loading is only 0.229 mg cm −2 . The prepared electrode exhibits the low overpotentials of 25.9 mV and 211 mV at the current densities of 10 and 100 mA cm −2, respectively, a small Tafel slope of 37.6 mV dec −1, and the excellent durability for HER. The porous network nanostructure of Pt/Ni(OH)2 hybrid, the large electrochemical surface area, the fast facilitated electron transport capability, and the firm adhesion of Pt nanodots with the anodized NF substrate contribute to the remarkable performance towards HER. Graphical abstract: Image 1 Highlights: A simple hydrothermal decomposition method was used to synthesize Pt nanodots. The anodized NF contributes to the porous network nanostructure of Pt/Ni(OH)2 hybrid. The modification of the NF substrate enhances the HER performance of the electrodes. The mechanisms of the efficient HER for the Pt/Ni(OH)2 /NF-A electrode are explained.